Industrial Maintenance System (IMS) Application Development for Heavy Equipment Inspection and Maintenance Processes at CV. Daya Putra Pratama - Ferizka Tiara Devani; Lailatur Rahmi; Muhamad Rizqon Yasir; Laras Ayu Anastasya (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
This research is motivated by the problem of inventory management and spare parts procurement at CV. Daya Putra Pratama, which is still done manually using spreadsheets and physical documents. This condition causes stock data discrepancies, delays in the procurement process, difficulties in monitoring procurement status, and limited information on spare parts availability for technicians. The resulting impacts include increased heavy equipment downtime, hampered maintenance activities, and decreased operational efficiency. To address these problems, a website-based Industrial Maintenance System application was developed that integrates stock management, purchase requests, purchase orders, inventory inspections, and supplier payment monitoring in one centralized platform. The Rapid Application Development method was used through the stages of requirements planning, design, and implementation. The development results show that the resulting application is able to improve inventory data accuracy, accelerate the procurement process, increase information transparency, and support more effective decision-making. Thus, the developed application can support increased operational efficiency and integrated inventory management and spare parts procurement.